The Mediating Role of Business Simulations on the Relationship between University Role Entrepreneurship Curriculum and Assessment of Teaching Approaches and Entrepreneurial Inclination - Mohd Sufli Yusof; Mohd Noor Mohd Shariff; Muhammad Salman Shabbir; Muhammad Shukri Bakar (International Journal of Supply Chain Management, 2018)
The primary purpose of the paper is provide an insight into present landscape of the role that universities are playing through entrepreneurship curriculum and business simulations in enhancing entrepreneurial inclination of the students through business simulations. The underlying theories of Experiential learning theory, Constructivist learning Theory and Blooms Taxonomy are described in relation with the objectives of the research. This study is conducted in the context of Malaysian Universities. The results of PLS-SEM illustrate that there is a significant positive mediating effect of business simulations on the relationship between entrepreneurship curriculum and contents, assessment of teaching approaches and entrepreneurial inclinations of students at Universiti Utara Malaysia. The present study aimed at providing an overview of the role that is assumed by the institutions of higher education whereas recommendations have been proposed for practitioners and researchers to cope with the challenges that higher education is facing currently. The future agenda of the research on similar lines has also been proposed.